Упростите выражение, срочно нужно

0 голосов
28 просмотров

Упростите выражение, срочно нужно


image

Алгебра (38 баллов) | 28 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

( \sqrt[4]{a} -1): \frac{ \sqrt[4]{a^3}+\sqrt[4]{a} - \sqrt{a} -1}{\sqrt{a}+a} = \frac{( \sqrt[4]{a} -1)\cdot \sqrt{a}\cdot (1+\sqrt{a})}{\sqrt[4]{a}\cdot (\sqrt{a}+1)-(\sqrt{a}+1)} =\\\\= \frac{(\sqrt[4]{a}-1)\cdot \sqrt{a}\cdot (1+\sqrt{a})}{(\sqrt{a}+1)\cdot (\sqrt[4]{a}-1)} =\sqrt{a}\\\\\\P.S.\; \; \sqrt[4]{a^3}+\sqrt[4]{a}=a^{\frac{3}{4}}+a^{\frac{1}{4}}=a^{\frac{1}{4}}\cdot (a^{\frac{3}{4}-\frac{1}{4}}+1)=a^{\frac{1}{4}}\cdot (a^{\frac{1}{2}}+1)=\\\\=\sqrt[4]{a}\cdot (\sqrt{a}+1)
(835k баллов)
0 голосов

Решите задачу:

( \sqrt[4]{a} -1): \frac{ \sqrt[4]{a^3}+ \sqrt[4]{a} - \sqrt{a} -1 }{ \sqrt{a}+a }= ( \sqrt[4]{a} -1): \frac{ \sqrt[4]{a}( \sqrt{a} + 1) -( \sqrt{a} +1) }{ \sqrt{a}( \sqrt{a} +1 )}==( \sqrt[4]{a} -1): \frac{( \sqrt[4]{a}-1)( \sqrt{a} + 1) }{ \sqrt{a}( \sqrt{a} +1 )}= ( \sqrt[4]{a} -1): \frac{ \sqrt[4]{a}-1 }{ \sqrt{a}}=( \sqrt[4]{a} -1)* \frac{ \sqrt{a} }{ \sqrt[4]{a}-1 } = \sqrt{a}
(4.5k баллов)